2006
DOI: 10.2140/pjm.2006.223.251
|View full text |Cite
|
Sign up to set email alerts
|

Existence of time-periodic solutions to the Navier–Stokes equations around a moving body

Abstract: We demonstrate the existence of time-periodic motions of an incompressible Navier-Stokes fluid subject to a time-periodic body force, occupying the region exterior to a body that performs a periodic rigid motion of same period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 17 publications
0
71
0
Order By: Relevance
“…In other words, one then obtains a time-periodic Navier-Stokes problem in a frame of reference that is given by the motion of the body, and which is not necessarily an inertial frame. This special type of time-periodic Navier-Stokes problem was investigated for the first time by Galdi and Silvestre in [25]. Galdi and Silvestre assumed a 1 Introduction prescribed motion of the body given by a time-periodic translational velocity ξ(t) and time-periodic angular velocity ω(t), which yields…”
Section: Historymentioning
confidence: 99%
See 4 more Smart Citations
“…In other words, one then obtains a time-periodic Navier-Stokes problem in a frame of reference that is given by the motion of the body, and which is not necessarily an inertial frame. This special type of time-periodic Navier-Stokes problem was investigated for the first time by Galdi and Silvestre in [25]. Galdi and Silvestre assumed a 1 Introduction prescribed motion of the body given by a time-periodic translational velocity ξ(t) and time-periodic angular velocity ω(t), which yields…”
Section: Historymentioning
confidence: 99%
“…Using a combination of an "invading domain" technique and the ProuseYudovich method, Galdi and Silvestre showed existence of a weak time-periodic solution to (1.7). In addition, existence of a strong solution is established in [25] under the assumption that the data ξ(t), ω(t), and f are sufficiently "small". In a further investigation of this problem, the same authors showed a few years later in [27] a similar result for the unconstrained motion of a body under the influence of a time-periodic body force, thereby extending a famous result of Weinberger [58,59] to the time-periodic case.…”
Section: Historymentioning
confidence: 99%
See 3 more Smart Citations